The Education of Home Herbal Utilization As Healthy Drink for Virus Antidote - Fita Sari; Fathul Hidayatul Hasanah; Farida Noor; Rosa Juwita Hesturini (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2023)
The herbal drink in Indonesia has a fast development for its easy usage and minimum side effect. Some house plants have metabolite compounds with an important role as antiviral such as rosella (Hibiscus sabdariffa), Curcuma domestica Val, Zingiber officinale, Cymbopogon citratus, and Pandanus amaryllifolius R. The purpose of our community empowerment activities was to introduce the benefits of house plants for supporting health, particularly as an antiviral during a pandemic. The method of community empowerment activities was carried out by explaining the example of home plants, their bioactive compound content, and their health benefits. The community was also taught to make simple and practical healthy drinks. The results showed that the community became more aware of the benefits of roselle and turmeric so that they did not doubt making a healthy drink to be consumed regularly during the pandemic. The results showed that about 85% of the community understood the benefits, and 90% were able to make herbal drinks. The conclusions of these community empowerment activities were going well. The community understood the benefits of house plants as an antiviral during a pandemic and succeeded in making simple healthy drinks from house plants.